Cervical Spinal Cord Injury with a Minor Trauma in A Patient with Ankylosing Spondylitis: A Case Report - Serpil Savaş,; Erdem İlgün,; Aşkın Görgülü,; Ahmet Yeşildağ, (Archives of Rheumatology, 2008)
Patients with advanced ankylosing spondylitis are prone to fractures of cervical spine following minor injuries. In this case report, we present a case of ankylosing spondylitis where the patient sustained cervical spinal cord injury after a minor traffic accident. (Rheumatism 2008 23: 28-30)